2021
DOI: 10.48550/arxiv.2102.07947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-band observations of Swift J0840.7-3516: a new transient ultra-compact X-ray binary candidate

F. Coti Zelati,
A. de Ugarte Postigo,
T. D. Russell
et al.

Abstract: We report on multi-band observations of the transient source Swift J0840.7−3516, which was detected in outburst in 2020 February by the Neil Gehrels Swift Observatory. The outburst episode lasted just ∼5 days, during which the observed X-ray flux quickly decreased from ∼ 1.8 × 10 −9 erg cm −2 s −1 at peak down to ∼ 1.3 × 10 −13 erg cm −2 s −1 in quiescence (0.3-10 keV). Such a marked and rapid decrease in the flux was also registered at UV and optical wavelengths. In outburst, the source showed considerable ap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It has been suggested that all confirmed UCXBs contain NS accretors, but the nature of accretors has not been identified exclusively in the observations (e.g. Sazonov et al 2020;Coti Zelati et al 2021). Note that UCXBs with BH accretors have not been confirmed, but there is a known moderately strong BH UCXB candidate 47 Tuc X9 in our Galaxy (see Bahramian et al 2017).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…It has been suggested that all confirmed UCXBs contain NS accretors, but the nature of accretors has not been identified exclusively in the observations (e.g. Sazonov et al 2020;Coti Zelati et al 2021). Note that UCXBs with BH accretors have not been confirmed, but there is a known moderately strong BH UCXB candidate 47 Tuc X9 in our Galaxy (see Bahramian et al 2017).…”
Section: Introductionmentioning
confidence: 85%
“…So far, there are about 40 known UCXBs or candidates, in which 15 of them have been identified with high confidence on the basis of the observed orbital periods (including 10 persistent sources and 5 transient sources; e.g. in 't Zand, Jonker & Markwardt 2007;Liu, van Paradijs & van den Heuvel 2007;Heinke et al 2013;Cartwright et al 2013;Coti Zelati et al 2021). It has been suggested that all confirmed UCXBs contain NS accretors, but the nature of accretors has not been identified exclusively in the observations (e.g.…”
Section: Introductionmentioning
confidence: 99%